ANALISA PERBANDINGAN EFEKTIVITAS PENDINGIN OLI HIDROLIK PADA MESIN FINE BLANKING PRESS 160T DENGAN MENGGUNAKN FAN RADIATOR DAN CHILLER - Suhariyanto; Solikin; Syahru Muharom, Muhammad (Universitas Muhammadiyah Surabaya, 2024)
The difficulty of stabilizing the temperature in the engine hydraulic system. PT. XYZ still hasn't found the best way or option to stabilize the temperature of the two 160T fine blanking press machines that require good hydraulic oil cooling, so the company wants to find out which is better by installing radiator fan cooling on the 160T A fine blanking machine or installing chiller cooler on the 160T B fine blanking machine. With that, data processing is carried out to determine the effectiveness of the two, and based on the data collected the 160T fine blanking press machine using a radiator fan cooler is more effective than using a chiller cooler. Keywords : Fan Radiator,Chiller, Efektivitas, Oil Hydraulic.